Does Postponing Minimum Retirement Age Improve Healthy Behaviors Before Retirement? Evidence from Middle-Aged Italian Workers - Marco Bertoni; Giorgio Brunello; Gianluca Mazzarella (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2017)
By increasing the residual working horizon of employed individuals, pension reforms that raise minimum retirement age are likely to affect individual investment in health-promoting behaviors before retirement. Using the exogenous variation in minimum retirement age induced by the sequence of Italian pension reforms during the 1990s and 2000s, we show that middle-aged Italian makes who were close to regiment age reacted to the expected longer working horizon by increasing regular exercise and by reducing smoking, with positive consequences for obesity and self-reported satisfaction with health.
Keywords: H55; I12; J26; 330; Retirement; Working Horizon; Healthy Behaviors; Pension Reforms